Pengaruh Konsentrasi Aktivator Terhadap Kualitas Karbon Aktif dari Batubara Lignit - Arif Nurrahman; Edwin Permana; Diah Riski Gusti; Intan Lestari (Universitas Batanghari Jambi, 2021)
Activated carbon has been widely used in everyday life. One of them is in water purification. Materials for making activated carbon have been made and researched. Coal is one of the materials that can be processed into activated carbon. The availability of coal in Indonesia is quite abundant and has the potential to be used as activated carbon. The coal used is lignite. This coal is categorized as light coal where its use is only used as fuel in industry. It is hoped that the activated carbon from this coal will become an alternative source of coal use in Indonesia. Activated carbon from coal uses a variable concentration of 0.5 M, 1 M, 1.5 M, 2 M, 2.5 M, 3 M with HCL activator solution. It is hoped that the results of this study are in accordance with the quality standard of SNI 06-3730-1995.